Managing labour relations in the correctional services: HR practitioner perspectives - Lene I. Graupner; Lesley I. Makau (SA Journal of Human Resource Management, 2025)
Orientation: Correctional services are high-stress, often violent environments marked by resource shortages, safety risks and deteriorating employee well-being. While much research focuses on the challenges faced by correctional officers, limited attention has been paid to human resource (HR) practitioners managing labour relations within this volatile context.